NEPHROPROTECTIVE EFFECT OF ALOE VERA EXTRACT WITH REGULATION OF OXIDATIVE STRESS, APOPTOSIS AND AQUAPORIN 3 EXPRESSION LEVELS IN STREPTOZOTOCIN INDUCED DIABETIC RATS - Seker, Ugur; Guzel, Baris Can; Sener-Akcora, Dila; Baygeldi, Saime Betul; Yuksel, Meral; Unay-Demirel, Ozlem; Soker, Sevda (University of Ankara, 2023)
Objective: In this study we examined the protective activity of Aloe vera with considering antioxidant, anti-apoptotic properties, and the status of Aquaporin 3 (AQP3) channel protein. Material and Method: Twenty-one adult female rats were divided into three groups (n=7); Control, Diabetes, Treatment. Control group did not expose to any application. Animals in Diabetes and Treatment were exposed to experimental diabetes with administration of streptozotocin. Rats in Treatment received 300 mg/kg Aloe vera extract daily for 14 days. Rats were sacrificed and kidney samples were used for analyses. Result and Discussion: Analyses indicated that lowest malondialdehyde (MDA) and luminol levels in control group were increased significantly (P<0.05) in diabetic animals. Severe pathological changes observed in Diabetes group while microscopic examinations. Bax, Caspase-3 and apoptotic index (AI) were elevated significantly (P<0.05) in this group compared to Control. Oxidative stress, apoptotic protein expression levels and TUNEL Assay positive cell ratio were down-regulated in Treatment group. When AQP3 levels were measured, immunopositivity reduced significantly (P<0.05) in cortical kidney of Diabetes group which is normalized significantly in Treatment group.This study reporting anti-diabetic potency of Aloe vera extract has capability to avoid streptozotocin induced diabetic renal injury via regulating anti-apoptotic and anti-oxidant cellular signaling. Furthermore, Aloe vera consumption in diabetes might regulate AQP3 levels. Although we observed promising results, more studies are required to explore anti-diabetic, anti-hyperglycemic and nephroprotective activity of Aloe vera. © 2023 Authors. All rights reserved.
ALOE VERA EKSTRAKTININ STREPTOZOTOSİN İNDÜKLÜ DİYABETIK RATLARDA OKSİDATİF STRESS, APOPTOZİS VE AQUAPORİN 3 EKSPRESYON DÜZEYİNİ DÜZENLEYEREK NEFROPROTEKTİF ETKİSİ
Keywords: Aloe vera; apoptosis; aquaporin 3; diabetes; kidney